(Un)resolving digital technology paradoxes through the rhetoric of balance. (January 2021) - Grigore, Georgiana; Molesworth, Mike; Miles, Chris; Glozer, Sarah
The organizational benefits of digital technologies are increasingly contrasted with negative societal consequences. Such tensions are contradictory, persistent and interrelated, suggesting paradoxes. Yet, we lack insight into how such apparent paradoxes are constructed and to what effect. This empirical paper draws upon interviews with thirty-nine responsibility managers to unpack how paradoxes are discursively (re)constructed and resolved as a rhetoric of 'balance' that ensures identification with organizational, familial and societal interests. We also reveal how such 'false balance' sustains and legitimizes organizational activity by displacing responsibilities onto distant 'others' through temporal (futurizing), spatial (externalizing) and level (magnifying / individualizing) rhetorical devices. In revealing the process of paradox construction and resolution as 'balance' in the context of digitalization and its unanticipated outcomes, we join conversations into new organizational responsibilities in the digital economy, with implications for theory and practice.